The Lacrimal System Diagnosis, Management, and Surgery, Second Edition - Cohen, Adam J.; Mercandetti, Michael; Brazzo, Brian (Springer International Publishing : Imprint: Springer, 2015)
While there are books that review lacrimal system disorders and surgery as a section of comprehensive oculoplastic textbooks, The Lacrimal System: Diagnosis, Management and Surgery solely addresses Lacrimology in one concise, practical volume. Building off of the success of the first edition, this text includes significantly updated information, new authors from around the world as well as new chapters that are complete with high quality images and illustrations. Lacrimal surgeries are commonly performed by oculoplastic surgeons and range from alleviating lacrimal system obstructions in children with congenital dysmorphology to minimally invasive lacrimal system reconstruction. The second edition of this book meets the needs of practicing physicians, fellows, and residents who are managing the tearing patient clinically and surgically.